2021
DOI: 10.1101/2021.11.23.469689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is categorization in visual working memory a way to reduce mental effort? A pupillometry study

Abstract: Recent studies on visual working memory (VWM) have shown that visual information can be stored in VWM as continuous (e.g., a specific shade of red) as well as categorical representations (e.g., the general category red). It has been widely assumed, yet never directly tested, that continuous representations require more VWM mental effort than categorical representations; given limited VWM capacity, this would mean that fewer continuous, as compared to categorical, representations can be maintained simultaneousl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This pattern—while complex—is consistent with previous findings that continuous and categorical representations each have a limited capacity, and that this limit is different for each type of representation. Specifically, Hardman and colleagues (2017) suggested that only a single continuous representation and two categorical representations can be maintained at the same time (see also Zhou et al, 2021 for converging evidence). In the current study, it is likely that at very short retention intervals (100 and 500 ms), visual information was still stored largely in iconic memory (Sperling 1960; or perhaps in ‘fragile working memory’; Sligte et al, 2008), which has a high capacity and relies on early visual cortex (Teeuwen et al, 2021); at this point, there was little (but some) categorical bias.…”
Section: Methodsmentioning
confidence: 99%
“…This pattern—while complex—is consistent with previous findings that continuous and categorical representations each have a limited capacity, and that this limit is different for each type of representation. Specifically, Hardman and colleagues (2017) suggested that only a single continuous representation and two categorical representations can be maintained at the same time (see also Zhou et al, 2021 for converging evidence). In the current study, it is likely that at very short retention intervals (100 and 500 ms), visual information was still stored largely in iconic memory (Sperling 1960; or perhaps in ‘fragile working memory’; Sligte et al, 2008), which has a high capacity and relies on early visual cortex (Teeuwen et al, 2021); at this point, there was little (but some) categorical bias.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that continuous representations are more fragile (Bae & Luck, 2019) and require more storage capacity as compared to categorical representations (Hardman et al, 2017;Zhou et al, 2022). This assumption is supported by the evidence that storing continuous representations appears to be more effortful than categorical representations, which limits the number of continuous representations that can be stored when memory load increases (Zhou et al, 2021). In a previous study, we asked participants to remember a varied number of colors (one to four); after a delay period of 100, 500, 1,000 or 2,000 ms, they had to report one of the memorized colors on a color circle (Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 93%
“…This is possibly because when storing precise, detailed information in VWM becomes (Panichello et al, 2019), but also in primates (Freedman et al, 2001, Panichello et al, 2019 and corvid (Apostel et al, 2023). The attractor dynamics model (Almeida et al, 2015;Panichello et al, 2019) suggests that as memory load increases, internal noise of memory errors (or "random diffusion") increases, while VWM is more biased towards certain nearby locations (or "attractors"), such as color prototypes (Bae et al, 2015;Zhou et al, 2021) and cardinal orientations (Bae, 2021). These attractors draw VWM towards a limited number of stable representations that mitigate the effect of noise, but at the same time, introduces bias.…”
Section: Working Memory Storage Is Supported By Multiple Brain Areas ...mentioning
confidence: 99%
“…As more research has been done to understand the strategies of working memory storage, increasing evidence has suggested that VWM storage cannot be simply explained by only the slot or the resource model (e.g., Pratte, 2020;Zhou et al, 2021). Although the slot-versus-resource debate is not the focus of this thesis, we propose that there are a limited number of slots for both continuous and categorical representations, and these slots have a variable precision depending on the need of the situation.…”
Section: How Does Working Memory Interact With Attention?mentioning
confidence: 99%
See 1 more Smart Citation